A Novel Glycosaminoglycan-binding Protein Is the Vertebrate Homologue of the Cell Cycle Control Protein, Cdc37 - Nicholas Grammatikakis; Aliki Grammatikakis; Masahiko Yoneda; Qin Yu; Shib D. Banerjee; Bryan P. Toole (1995)
Using a monoclonal antibody, IVd4, that recognizes a novel group of hyaluronan-binding proteins, we have immunoscreened a cDNA library constructed from embryonic chick heart muscle mRNA. One of the cDNAs isolated from the library encodes a 29.3-kDa protein homologous to Cdc37, an essential cell cycle regulatory factor previously characterized genetically in yeast and Drosophila; this is the first vertebrate CDC37 gene to be cloned to date. We also present evidence for the existence of a second chick isoform that is identical to the 29.3-kDa protein over the first 175 amino acids but is entirely different at the carboxyl terminus and lacks the IVd4 epitope. The avian Cdc37 binds hyaluronan, chondroitin sulfate and heparin in vitro, and both isoforms contain glycosaminoglycan-binding motifs previously described in several hyaluronan-binding proteins. These findings suggest a role for glycosaminoglycans in cell division control.